Otherness and Self in Latvian Theatre: Changes at the Turn of the Nineteenth Century - Daija, Pauls (Nordic Theatre Studies, 2015)
In the article, political and historical interpretations of the first play in Latvian, an adapted translation of Ludvig Holberg’s Jeppe of the Hill (1723, Latvian version 1790) are explored. Although the play has been often interpreted as a work of anti-alcohol propaganda, the article argues that the political motives of the play are no less important. Translated into Latvian during the time of the French revolution, the play mirrors the tense atmosphere of the revolutionary years and reflects changes in Latvian peasant identity. While translating, Baltic German pastor Alexander Johann Stender changed the play’s setting to the late eighteenth century Courland and added new details, emphasizing the social conflict of the play as an ethnic one. It has been argued in the article that since ‘class’ in the Baltics was divided along national lines, the difference between peasants and masters was also the difference between Latvians and Germans, so class and ethnicity merged. When the peasant and the nobleman switch places in the play, this symbolizes a change in the Latvian-German colonial relationship. The colonial interpretation allows for a characterisation of the protagonist as a desperate imitator – a colonial subject who loses his identity as a serf and is not able to form a new identity in any way other than by copying the colonialist op- pressor. But this mimicry turns into ridicule, hence the play acquires a political meaning as it implicitly shows the disastrous consequences of revolutionary pro- test. Therefore, the play can be read as a part of the discussions about the Baltic Enlightenment emancipation project and as a hidden debate on serfdom and the colonial framework of the Courland society